Effects of post-activation potentiation exercises on kicking frequency, fatigue rate and jump performance in taekwondo athletes: a case study (Efectos de los ejercicios de potenciación post activación sobre la frecuencia de pateo, tasa de fatiga y saltabi - Castro-Garrido, Nibaldo; Valderas-Maldonado, Carol; Herrera-Valenzuela, Tomás; Ferreira Da Silva, Jonatas; Guzmán-Muñoz, Eduardo; Vásquez-Gómez, Jaime; Magnani Branco, Braulio; Zapata-Bastias, José; Valdés-Badilla, Pablo; López-Fuenzalida, Antonio (Retos, 2020)
Abstract. The aim of the present study was to establish the effects of three conditions of post-activation potentiation (PAP) exercises on kicking frequency, fatigue rate (FR) and jump performance in novice and advanced taekwondo athletes. Secondarily, to establish if the PAP strength plus plyometrics exercises produced a significantly higher increase with respect to exercises of isolated strength and plyometrics. Eight university taekwondo athletes (n=4 novices and n=4 advanced) were randomized into four (one control and three experimental) intervention conditions. Kicking frequency and FR were evaluated with the Frequency Speed of Kicks Test (FSKT), and countermovement jump test (CMJ). Effect size (ES) was calculated and the significance level was stabilized at p